1989
DOI: 10.1007/bf02207237
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of the osteoporotic vertebral fracture

Abstract: The clinical picture of the osteoporotic fractures of the spine presents an heterogeneity in their intensity and duration. In 210 cases of osteoporotics with acute pain and radiological evidence of spinal fracture we separate their clinical picture in two groups. In Type I (121 cases) pain is acute and severe, improving gradually; the vertebral wedging is obvious from the beginning and remain unchanged. The duration of this event exceeds 4-8 weeks. In Type II (89 cases) pain is less and of shorter duration, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
10

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 4 publications
0
48
0
10
Order By: Relevance
“…These include short vertebral height (SVH), which they report as being more common in older, heavier women, unrelated to osteoporosis [40,41], equally prevalent in preand postmenopausal women [41], and therefore unimportant. However, the limited evidence on the natural history of "mild" vertebral deformities suggests that they do predict subsequent fracture [5] and may even represent an epidemiologically distinct subtype of vertebral "fractures" [42]. This may also explain the different demographic pattern of women with SVH between pre-and postmenopausal women in Ferrar and colleagues' comparison of these groups [41].…”
Section: Discussionmentioning
confidence: 88%
“…These include short vertebral height (SVH), which they report as being more common in older, heavier women, unrelated to osteoporosis [40,41], equally prevalent in preand postmenopausal women [41], and therefore unimportant. However, the limited evidence on the natural history of "mild" vertebral deformities suggests that they do predict subsequent fracture [5] and may even represent an epidemiologically distinct subtype of vertebral "fractures" [42]. This may also explain the different demographic pattern of women with SVH between pre-and postmenopausal women in Ferrar and colleagues' comparison of these groups [41].…”
Section: Discussionmentioning
confidence: 88%
“…When an acute OVCF occurs, the pain may be so devastating and disabling that hospital admission is required; length of stay for such fractures may be as long as 10 to 14 days [6][7][8]. On the other hand, OVCFs may be associated with mild back pain and stiffness, and the diagnosis of a fracture often goes unnoticed [9].…”
Section: Description Of the Conditionmentioning
confidence: 98%
“…Previous studies have found that medical management of symptomatic VCFs often fails to improve pain and mobility particularly in cases of chronic pain related to kyphotic deformity [27,31,41]. Furthermore, long-term use of narcotic analgesics and anti-inflammatory drugs are poorly tolerated by elderly patients.…”
Section: Introductionmentioning
confidence: 96%